Complex forms of education for students of a special medical group in the elective discipline «Physical culture and sports» - Podberezko N.A. ,; Novichikhina E.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the effectiveness of various forms of training in educational programs for students of a special medical group during practical classes in physical education. Methods and structure of the study. 171 students of special medical group “A” took part in the experiment. A pedagogical experiment on the implementation of educational programs using electronic educational technologies was carried out on the basis of Altai State University in the period from 2018 to 2020. Results and conclusions. Based on the results of the survey, the effectiveness of the educational program was proven, which included the traditional (contact work) form of education and the use of electronic educational technologies (electronic course), in order to increase awareness, interest and desire to increase one’s physical activity and engage in physical education. The need to expand the educational program for students with health problems is outlined, expressed in the introduction of theoretical and educational materials that can be implemented through electronic educational technologies. Conclusion. The inclusion of the proposed classes in the curriculum of elective disciplines “Physical Culture and Sports” for students with health problems allows you to increase the quality of knowledge and skills necessary for the implementation of physical activity with individual consideration of diseases, as well as independently select physical exercises and their dosage for organizing independent exercises in order to stabilize existing health deviations, exercise self-control and psychomotor development, and increase motivation for exercise.